The embryarian annexes of birds: literature review (Research, Society and Development, 2021)
In order for viviparous vertebrates, including birds that have their embryonic development inside the egg, to be able to survive in the embryonic period, they need embryonic attachments (amnion, corium, allantois and yolk sac). Despite being a relevant subject, there was still no literary survey that demonstrated the disposition, training, function, use in lines of research and specific aspects of these annexes in the most diverse birds, having this in mind, the purpose of this review is to make this survey, the review presents a qualitative type study of bibliographic research with descriptive characteristics and provided information that helps to understand various mechanisms during the formation of the embryo and the progress of development within the egg, as a future perspective this research is expected to serve as a boost so that new research in the area is developed that can also promote scientific development.